Biological rhythms in Arctic vertebrates - van Oort, B. E.H.; Tyler, N. J.C.; Reierth, E.; Stokkan, K.-A. (Rangifer, 2000)
Many biological processes show regular cyclical fluctuations that persist throughout an organism's life; these range from the transcription of DNA to patterns of behaviour. Persistent, cyclical phenomena of this kind are a fundamental feature of all organisms. They are governed primarily by endogenous rhythms generated by a 'biological clock' situated in the brain. Normally, however, the expression of the clock is modulated to a greater or lesser extent by environmental cues. This paper reviews the physiological control of the temporal organisation of cycles in vertebrates and, in particular, explores their regulation in arctic species like reindeer (Rangifer tarandus L.). We emphasise how exposure to the photoperiodic conditions that characterise polar regions places special demands on timing mechanisms and how arctic species, therefore, are of particular interest for the study of biological rhythms. Thus far, behavioural and physiological studies of these species show that arctic reindeer (and ptarmigan) appear to be truly opportunistic in summer and wintet, seemingly without any active biological clock and that they are, instead, driven directly by photoperiod. This situation, if confirmed, would be unique among vertebrates.